Prognostic Value of Clinical vs Pathologic Stage in Rectal Cancer Patients Receiving Neoadjuvant Therapy. (20th November 2017) - Delitto, Daniel; George, Thomas J; Loftus, Tyler J; Qiu, Peihua; Chang, George J; Allegra, Carmen J; Hall, William A; Hughes, Steven J; Tan, Sanda A; Shaw, Christiana M; Iqbal, Atif
Abstract: Background: Neoadjuvant chemoradiation is currently standard of care in stage II–III rectal cancer, resulting in tumor downstaging for patients with treatment-responsive disease. However, the prognosis of the downstaged patient remains controversial. This work critically analyzes the relative contribution of pre- and post-therapy staging to the anticipated survival of downstaged patients. Methods: The National Cancer Database (NCDB) was queried for patients with rectal cancer treated with transabdominal resection between 2004 and 2014. Stage II–III patients downstaged with neoadjuvant radiation were compared with stage I patients treated with definitive resection alone. Patients with positive surgical margins were excluded. Overall survival was evaluated using both Kaplan-Meier analyses and Cox proportional hazards models. All statistical tests were two-sided. Results: A total of 44 320 patients were eligible for analysis. Survival was equivalent for patients presenting with cT1N0 disease undergoing resection (mean survival = 113.0 months, 95% confidence interval [CI] = 110.8 to 115.3 months) compared with those downstaged to pT1N0 from both cT3N0 (mean survival = 114.9 months, 95% CI = 110.4 to 119.3 months, P = .12) and cT3N1 disease (mean survival = 115.4 months, 95% CI = 110.1 to 120.7 months, P = .22). Survival statistically significantly improved in patients downstaged to pT2N0 from cT3N0 disease (mean survival = 109.0 months, 95% CI = 106.7 to 111.2 months, P < .001) and cT3N1 (mean survival = 112.8 months, 95% CI = 110.0 to 115.7 months, P < .001), compared with cT2N0 patients undergoing resection alone (mean survival = 100.0 months, 95% CI = 97.5 to 102.5 months). Multiple survival analysis confirmed that final pathologic stage dictated long-term outcomes in patients undergoing neoadjuvant radiation (hazard ratio [HR] of pT2 = 1.24, 95% CI = 1.10 to 1.41; HR of pT3 = 1.81, 95% CI = 1.61 to 2.05; HR of pT4 = 2.72, 95% CI = 2.28 to 3.25, all P ≤ .001 vs pT1; HR of pN1 = 1.50, 95% CI = 1.41 to 1.59; HR of pN2 = 2.17, 95% CI = 2.00 to 2.35, both P < .001 vs pN0); while clinical stage at presentation had little to no predictive value (HR of cT2 = 0.81, 95% CI = 0.69 to 0.95, P = .008; HR of cT3 = 0.83, 95% CI = 0.72 to 0.96, P = .009; HR of cT4 = 1.02, 95% CI = 0.85 to 1.21, P = .87 vs cT1; HR of cN1 = 0.96, 95% CI = 0.91 to 1.02, P = .19; HR of cN2 = 0.96, 95% CI = 0.86 to 1.08, P = .48 vs cN0). Conclusions: Survival in patients with rectal cancer undergoing neoadjuvant radiation is driven by post-therapy pathologic stage, regardless of pretherapy clinical stage. These data will further inform prognostic discussions with patients.